Interaction between the endangered freshwater pearl mussel Margaritifera margaritifera, the duck mussel Anodonta anatina and the fish host (Salmo) : acquired and cross-immunity - Chowdhury, Motiur; Salonen, Jouni; Marjomäki, Timo; Taskinen, Jouni (Hydrobiologia, 2018)
The common duck mussel Anodonta anatina can live in sympatry with—and use the same host, brown trout (Salmo trutta)—as the endangered freshwater pearl mussel Margaritifera margaritifera. Since the glochidia release of A. anatina takes place seasonally earlier than that of M. margaritifera, brown trout can be sequentially exposed first to A. anatina and then to M. margaritifera. Cross-immunity, an immune reaction induced in fish host against glochidia after the infection with glochidia of another mussel species, is possible. Thus, it was studied experimentally if brown trout can be cross immunized against M. margaritifera by earlier infection with A. anatina. In addition, the hypothesis that consecutive exposures of same glochidial species in different years in the same host may create acquired immunity was tested in brown trout against M. margaritifera. Furthermore, the dose dependence of acquired immunity against M. margaritifera glochidia in the Atlantic salmon (S. salar) was also studied. Cross-immunity was not found; suggesting that occurrence of A. anatina does not pose a threat to M. margaritifera. Instead, acquired immunity and its dose dependence were evident, emphasizing the significance of availability of 0+ age group immunologically naïve Atlantic salmon/brown trout for efficient conservation of M. margaritifera. peerReviewed